Penyuluhan Pentingnya Vaksinasi Covid 19, Pelatihan Pencegahan Deman Berdarah Dengue dan Edukasi kesehatan Gigi untuk Kader Kesehatan Kecamatan Palmerah, Jakarta Barat - Juslily, Marta; Eddy; Ariesanti, Yessy; Handjojo, James; Kusumaratna, Rina (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
In November 2021, Covid-19 vaccination coverage in the special capital area (DKI) Jakarta stage 1 (one) reached 78.1% and stage 2 (two) 60.4% for local identity cards (KTP) DKI Jakarta. Covid-19 vaccination coverage for area the Palmerah District stage 1 (one) has reached 96.56% but unfortunately for stage 2 (two) it has not met the expected target. In order to reduce the Covid-19 case, the regional administration (Pemda) of DKI Jakarta has continued given education and socialization to increase public awareness in implementing health protocols and providing Covid-19 vaccinations to the public.Another problem that occurs in the Palmerah District is the increase cases of Dengue Hemorrhagic Fever (DHF). This increase is due to the rainy season which is the breeding time for the Aedes Aegepty mosquito. DHF can be prevented through controlling the Mosquito Nest Eradication (PSN) programme. Public awareness for healthy behavior and maintaining a mosquito-free home environment is still lacking therefor counseling and training are needed for the community to prevent dengue.Since the Covid 19 pandemic, the Dental Health Education Program could not be implemented in Palmerah Health Center due to pandemic and limited resources. Providing dental health education (DHE) to health cadres will increase oral health in community. The results obtained after the training significantly increased the knowledge of the cadres and community members who participated in the event. Thus this collaboration program should continue regularly to maintain knowledge and health practice in community.